Biomedical Optics and 3-D Imaging 2010
DOI: 10.1364/biomed.2010.btud96
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Abnormal Motor Cortex Activation Patterns in Children with Cerebral Palsy by Functional Near Infrared Spectroscopy

Abstract: Abstract. We demonstrate the utility of functional near-infrared spectroscopy ͑fNIRS͒ as a tool for physicians to study cortical plasticity in children with cerebral palsy ͑CP͒. Motor cortex activation patterns were studied in five healthy children and five children with CP ͑8.4± 2.3 years old in both groups͒ performing a finger-tapping protocol. Spatial ͑distance from center and area difference͒ and temporal ͑duration and time-to-peak͒ image metrics are proposed as potential biomarkers for differentiating abn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In unilateral CP, fNIRS has been used to assess brain activation during hand movements ( Tian et al, 2008 ; Tian et al, 2010 ; Khan et al, 2010 ; Decampos et al, 2016 ), and to evaluate pre-frontal cortical activation in bilateral CP during a throwing task ( Chaudhary et al, 2014 ). With respect to the lower extremity, one study evaluated fNIRS activation during gait in four children with bilateral CP compared to eight children with typical development (TD).…”
Section: Introductionmentioning
confidence: 99%
“…In unilateral CP, fNIRS has been used to assess brain activation during hand movements ( Tian et al, 2008 ; Tian et al, 2010 ; Khan et al, 2010 ; Decampos et al, 2016 ), and to evaluate pre-frontal cortical activation in bilateral CP during a throwing task ( Chaudhary et al, 2014 ). With respect to the lower extremity, one study evaluated fNIRS activation during gait in four children with bilateral CP compared to eight children with typical development (TD).…”
Section: Introductionmentioning
confidence: 99%
“…Near‐infrared spectroscopy (NIRS) is a well‐established method for measuring oxygen saturation and oxidative capacity in skeletal muscle and cerebral tissue (Khan et al . ; Tian et al . ; Ryan et al .…”
Section: Introductionmentioning
confidence: 99%
“…3 Technological advances have recently enabled the use of functional near-infrared spectroscopy (fNIRS) to study sensorimotor brain activity. [4][5][6] fNIRS non-invasively measures changes in the concentrations of hemoglobin species associated with neuronal activation providing a unique opportunity to study brain activity during functional tasks in populations with movement disorders who may not be able to remain sufficiently still for testing. fNIRS does not require participants to be confined and is relatively robust to movement artifacts.…”
mentioning
confidence: 99%
“…Studies using various imaging techniques have revealed some mechanisms underlying unimanual impairments in unilateral CP and highlighted the neuroplastic potential in children with this condition . Technological advances have recently enabled the use of functional near‐infrared spectroscopy (fNIRS) to study sensorimotor brain activity . fNIRS non‐invasively measures changes in the concentrations of hemoglobin species associated with neuronal activation providing a unique opportunity to study brain activity during functional tasks in populations with movement disorders who may not be able to remain sufficiently still for testing.…”
mentioning
confidence: 99%